Atitudes linguísticas dos alunos da educação de jovens e adultos do ensino fundamental - Morais, Ana Paula Nunes da Silva (2024)
In this work, I conducted a study on the Linguistic Attitudes of EJAEF (1st Stage) students from a state public school located in the municipality of Areia Branca-SE. The interest in this topic arose from observing that students showed great difficulty in expressing themselves orally during classes, as well as in certain school settings where the majority of the audience consisted of residents from the urban area. Thus, the research was justified by the need to increase the linguistic self-esteem of the social actors involved. Negative attitudes toward the various linguistic forms existing in our country can lead to linguistic prejudice, which may result in negative consequences in people’s lives. Therefore, the general objective was to investigate the linguistic attitudes of EJAEF students regarding their own speech. For this, I developed a pedagogical tool aimed at increasing students’ linguistic self-esteem. This educational product consisted of a Pedagogical Workbook titled Positively Evaluating the Variety We Use, which provided support for the professional practices of teachers in Basic Education. Among the authors consulted to support this research are Lambert and Lambert (1967), Bem (1973), and Morales (1993), focusing on linguistic attitudes; Huizinga (1996) on the concept of play; Bagno (2001, 2014) with studies on linguistic variety; Bortoni-Ricardo (2004, 2014) on educational sociolinguistics; and Faraco (2008) on defining and exemplifying normative concepts. This study is based on an Autoethnographic methodology, a qualitative research approach that involves exploring and reflecting on the researcher’s personal experience as a source of data and knowledge, as noted by Santos (2017), along with Action Research as conceived by Thiollent (1986), an empirical social research type designed and conducted in close association with action or solving a collective problem. Data collection was carried out through activities that reflected the subjects’ views on their Linguistic Attitudes. Ultimately, the results were achieved through the students’ oral expression, as well as an increase in linguistic self-esteem and respect for linguistic diversity.